Analisis Pemberdayaan Ekonomi Masyarakat Objek Wisata Floating Market Lembang - Fauzi, Ahmad; Fikrurrijal, Mohammad (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2023)
Regional governments in Indonesia have a big task in improving the welfare of their communities. One of these efforts is to build the Lembang Floating Market tourist industry which has been open since the beginning of December 2012. The aim of building the Lembang floating market tourist attraction is in the context of community empowerment and what is the reality now that community empowerment and community welfare are increasing. This research uses a descriptive method which is qualitative research using observation and interviews. The results of this research state that one form of empowerment of the Lembang community can be seen in the construction of the Floating Market tourist attraction which not only provides benefits to the Floating Market, but also provides opportunities for the community around the tourist attraction such as employment opportunities by opening employment opportunities, entrepreneurship opportunities, and also the existence of Floating Market income, part of which will then be included in the village PAD. The existence of the Lembang Floating Market does have a positive impact, but it cannot be denied that there are also negative impacts. One of the negative impacts is that traffic jams often occur due to the large number of vehicles entering and exiting the Floating Market. Apart from that, the large number of automatic vehicles also causes noise pollution. However. Whatever the positive and negative impacts, it cannot be denied that the existence of the Lembang Floating Market has had an impact on the community's economy, especially the Lembang village community.